MANAGING TECHNOLOGICAL TRANSITIONS: LCA, TCO AND ECONOMIC BENEFIT ANALYSIS OF COMBINE TRACTOR TERMINAL ELECTRIFICATION IN A SEAPORT (CASE STUDY: PT PELINDO TERMINAL TELUK LAMONG) - Afifah, Nur
This research addresses the urgent need to transition Combined Tractor Terminals (CTTs) towards electrification within the maritime context, focusing on Terminal Teluk Lamong (TTL) in Indonesia. The study begins by establishing a baseline for emissions and cost levels associated with conventional diesel-powered CTTs, based on historical data and current operational conditions at TTL. Through a Life Cycle Assessment (LCA), the research quantifies the environmental impacts, including emissions of CO2, NOx, and particulate matter (PM), across the lifecycle of the CTTs.